Study of Tourism Literature in Novel through a Genetic Structuralism Approach - Satinem, Satinem; Juwati, Juwati; Noermanzah, Noermanzah; Sumiharti, Sumiharti (UNIB Press, 2024)
Amanda, A. P., Syamsina, A. N., & Pratiwi, I. I. (2024). Strukturalisme genetik Lucien Goldmann dalam novel Supernova 2: Akar karya Dee Lestari (Lucien Goldmann's genetic structuralism in the novel Supernova 2: Akar by Dee Lestari). Aksarabaca Jurnal Bahasa, Sastra, dan Budaya, 1(1), 1–11. https://doi.org/10.47313/aksarabaca.v1i1.3138 Anoegrajekti, D. (2020). Sastra pariwisata (Tourism literature). Yogyakarta: Kanisius. Arnas, B. (2021). Ethile-Ethile. Yogyakarta: Diva Press. Artawan, G. (2020). Aku cinta lovina: Peran sastra dalam mempromosikan pariwisata Bali Utara (I love Lovina: The role of literature in promoting tourism in North Bali). JUMPA, 7(1), 241–256. Artika, I W. (2021). Pengembangan pariwisata sastra di Desa Kalibukbuk (Development of literary tourism in Kalibukbuk Village). Prosiding Jurusan Bahasa Sastra Indonesia dan Daerah, Universitas Pendidikan Ganesha, Singaraja. Atkinson, W. (2016). Beyond bourdieu: From genetic structuralism to relational phenomenology. Cambridge: Polity Press. Barnet S., Burto W., & Cain, W. E. (2018). An introduction to literature: Fiction, poetry, and drama (15th ed). New York: Pearson Longman. Burhan, N. (2007). Teori pengkajian fiksi (Fictional study theory). Yogyakarta: Gadjah Mada Universty Press. Butler, C. (2020). Japan reads the cotswolds: Children’s literature, tourism, and the Japanese imagination. Children’s Literature, 48(1), 198–233. https://doi.org/10.1353/chl.2020.0008 Castle, G. (2013). The literary theory handbook. London: Wiley Blackwell. Djumati, R., Jaya, A., & Rauf, R. (2023). Sosialisasi pelestarian sastra pariwisata tradisional Ternate: Studi pariwisata dan sastra interdisiplin (Socialization of the preservation of traditional Ternate tourism literature: Interdisciplinary tourism and literature studies). Jurnal Altifani Penelitian dan Pengabdian Kepada Masyarakat, 3(4), 620–629. https://doi.org/10.59395/altifani.v3i4.470 Ermila, M., Fadlillah, F., & Zurmailis, Z. (2022). Pandangan dunia pengarang dalam trilogi novel Rapijali karya Dee Lestari: Tinjauan strukturalisme genetik Goldmann (The author's worldview in the Rapijali novel trilogy by Dee Lestari: A review of Goldmann's genetic structuralism). Puitika, 18(2), 18. https://doi.org/10.25077/puitika.18.2.16-33.2022 Faruk, (2017). Metode penelitian sastra (Literary research methods). Yogyakarta: Pustaka Pelajar. Faruk. (2015). Pengantar sosiologi sastra dari strukturalisme genetik sampai post- modernisme (Introduction to the sociology of literature from genetic structuralism to post-modernism). Yogyakarta: Pustaka Pelajar. Himes, M. (2022). Visual novel based education in English literature: A study on student engagement. Press Start, 8(2), 1–20. https://press-start.gla.ac.uk/index.php/press-start/article/view/206 Holland, K. (2013). The novel in the age of disintegration: Dostoevsky and the problem of genre in the 1870s. Evanston: Northwestern University Press, Intan, T. (2021). Novel L’homme Qui Voulait Être Heureux karya laurent gounelle dalam perspektif kajian pariwisata sastra (The novel L’homme Qui Voulait Être Heureux by Laurent Gounelle from the perspective of literary tourism studies). Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 9(2), 395. https://doi.org/10.20961/basastra.v9i2.51802 Kamila, A., Fathurohman, I., & Kanzunnudin, M. (2023). Fakta kemanusiaan dalam novel Ronggeng Dukuh Paruk karya Ahmad Tohari kajian strukturalisme genetik Lucien Goldmann (Facts about humanity in the novel Ronggeng Dukuh Paruk by Ahmad Tohari, a study of Lucien Goldmann's genetic structuralism). Edukasiana: Jurnal Inovasi Pendidikan, 2(1), 33–39. https://doi.org/10.56916/ejip.v2i1.246 Noermanzah, N. N. (2017). Plot in a collection of short stories “Sakinah Bersamamu” works of Asma Nadia with feminimism analysis. Humanus, 16(1), 27. https://doi.org/10.24036/jh.v16i1.7015 Nyoman, R. K. (2019). Sastra pariwisata: Pendekatan interdisipliner kajian sastra dan pariwisata (Tourism literature: An interdisciplinary approach to literary and tourism studies). Seminar Nasional INOBALI, (2005), 173–181. Riana, D. R. (2020). Wajah pasar terapung sebagai ikon wisata Banjarmasin, Kalimantan Selatan dalam sastra: Kajian sastra pariwisata (The face of the floating market as a tourist icon in Banjarmasin, South Kalimantan in literature: A study of tourism literature). Undas, 16(2), 231–250. https://doi.org/10.26499/und.v16i2.2808 Sangidu. (2004). Penelitian sastra: Pendekatan, teori, metode, teknik, dan kiat (Literary research: Approaches, theories, methods, techniques and tips). Yogyakarta: Gajah Mada. Satinem, S., Juwati, J., & Noermanzah, N. (2020). Developing teaching material of poetry appreciation based on students competency analysis. English Review: Journal of English Education, 8(2), 237. https://doi.org/10.25134/erjee.v8i2.2707 Sunarti, S. (2020). Pemberdayaan cerita rakyat untuk pengembangan destinasi wisata berbasis kekayaan budaya Indonesia (Empowerment of folklore for the development of tourist destinations based on Indonesia's cultural richness). Jakarta: Badan Pengembangan dan Pembinaan Bahasa. Wellek, R. & Warren, A. (1977). Theory of literature. London: Harcourt Brace Javanovich Publisher. Wibowo, S. (2020). Sastra pariwisata: Perjalanan pengembangan budaya (Tourism literature: A journey of cultural development). Yogyakarta: Kanisius. Wicaksono, A. (2017). Kearifan pada lingkungan hidup dalam novel-novel karya Andrea Hirata (Tinjauan strukturalisme genetik) (Wisdom on the environment in novels by Andrea Hirata (Review of genetic structuralism)). JENTERA: Jurnal Kajian Sastra, 5(1), 7. https://doi.org/10.26499/jentera.v5i1.346 Yasa, I N. (2012). Teori sastra dan penerapannya (Literary theory and its application). Bandung: Karya Putra Darwati.